Renewable energy research in Malaysia - Islam, M.R.; Saidur, Rahman; Rahim, N.A.; Solangi, K.H. (University of Malaya, 2009)
Malaysia is one of the most developing ASEAN countries, with a GDP of US14,700 per capita (PPP basis), and steady GDP growth of 5.5 in 2008. Malaysia is in the midst of an era of vigorous industrial growth brought about by strong domestic demand together with its significant science and technology development. To cope with the economical and industrial growth, the demand of energy is growing very rapidly. In this paper the energy related policies of Malaysia have been discussed. The present status of renewable energy in Malaysia has been also discussed in the paper as well. It has been found that among all the renewable energy sources, solar energy is the most prospective one in Malaysia.